Radical Solutions and Open Science An Open Approach to Boost Higher Education - Burgos, Daniel; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This open access book presents how Open Science is a powerful tool to boost Higher Education. The book introduces the reader into Open Access, Open Technology, Open Data, Open Research results, Open Licensing, Open Accreditation, Open Certification, Open Policy and, of course, Open Educational Resources. It brings all these key topics from major players in the field; experts that present the current state of the art and the forthcoming steps towards a useful and effective implementation. This book presents radical, transgenic solutions for recurrent and long-standing problems in Higher Education. Every chapter presents a clear view and a related solution to make Higher Education progress and implement tools and strategies to improve the user$1 (Bs performance and learning experience. This book is part of a trilogy with companion volumes on Radical Solutions & Learning Analytics and Radical Solutions & eLearning.s
1 Open Science as a way of Education Diversity -- 2 Open Licensing, Publishing and Accreditation -- 3 Integration of Formal and Informal Education Through Open Content -- 4 Open Data and Research Processes -- 5 Open Educational Resources: Development -- 6 Open Educational Resources: Assessment -- 7 Open Educational Resources: Quality -- 8 Open, Universal and Free Access to Education -- 9 Open Software as Cultural Heritage -- 10 Integration of Open Science with Regular Academic Programmes -- 11 The Student as a Center of His Learning Itinerary. The Prosumer Role -- 12 The Teacher as a Facilitator of the Student$1 (Bs Self-Learning Itinerary. The Mentoring Role -- 13 The Institution as an Ecosystem for Integration and Learning Sharing -- 14 Case Study 1: Practical Use of Open Science in the Classroom -- 15 Case Study 2: Practical Use of Open Science in the Classroom.s
Keywords: Educational technology; Learning, Psychology of; Education, Higher; Digital Education and Educational Technology; Instructional Psychology; Higher Education